Processes and Strategies of Translating Joyce: Stephen Hero as a Case in Point - O’Shea, José Roberto (ABEI Journal, 2016)
This essay was read by the author as the second Maria Helena Kopschitz Annual Lecture, delivered at The University College, Dublin, James Joyce Centre, on 25 February 2016. The piece starts from an overview of Joyce’s translations in Brazil and proceeds to draw on thoughts stemming from the author’s own experience translating James Joyce’s fiction,  especially Dubliners and Stephen Hero into Brazilian Portuguese.Keywords: James Joyce; Stephen Hero; translation in Brazil.